MPS 13-01 NOVEL THERAPEUTIC APPROACH FOR CEREBRAL ISCHEMIA IN RATS WITH ANGIOTENSIN II PEPTIDE VACCINE. (September 2016) - Nakagami, Hironori; Wakayama, Kouji; Shimamura, Munehisa; Suzuki, Jun-ichi; Watanabe, Ryo; Koriyama, Hiroshi; Isobe, Mitsuaki; Rakugi, Hiromi; Morishita, Ryuichi
Abstract : Objective: We recently reported the efficacy of angiotensin II (Ang II) peptide vaccine for hypertension in mice and rats. The purpose of this study is to investigate whether pre-exposure Ang II vaccination exhibits the cerebroprotective effects after permanent middle cerebral artery occlusion (pMCAo) in rats. Design and Method: After subcutaneous injection of Ang II peptide vaccine (10 μg/200 μl) or saline (200 μl) to SD rats (male, 4week-old) at the time point of 4, 6 and 7 week-old, MCAo or sham surgery was performed at 8 week-old. The plasma Ang II antibody titer or brain parenchymal Ang II antibody level was quantified using ELISA. Serial sections were stained with cresyl violet to measure infarction volume. Neuronal degeneration and oxidative stress were evaluated using Fluoro Jade B (FJB) and 4-Hydroxynonenal (4-HNE) staining. The expression of brain renin-angiotensin-system (RAS) components or NOX2 was quantified using real-time PCR. Results: Systemic blood pressure was not affected by vaccination. Infarction volume at 24 hours after MCAo was reduced not in plasma low-titer (VL ) group (OD 50% < 6000) but in plasma high-titer (VH ) group (OD5 0% ≧ 6000) compared to saline treated control (C) group. Parenchymal anti-Ang II antibody level in the ischemic hemisphere was significantly higher in VH group compared with VL group. Both FJB positive neurons and 4-HNE positive cells were significantly decreased in VH group. The expression of brain Ang II type 1 receptor mRNA and brain NOX2 mRNA were less in VH group compared with C group. Conclusions: Ang II vaccination ameliorates ischemic injury in pMCAo rats. The possible mechanisms of protective effect of Ang II peptide vaccine in cerebral ischemia were its inhibitory effects against brain RAS and /or anti-oxidative effects. Therapeutic vaccination targeting Ang II may be a promising approach to treat cerebral ischemia.